Procalcitonin-Guided Use of Antibiotics for Lower Respiratory Tract Infection - Huang, David T; Yealy, Donald M; Filbin, Michael R; Brown, Aaron M; Chang, Chung-Chou H; Doi, Yohei; Donnino, Michael W; Fine, Jonathan; Fine, Michael J; Fischer, Michelle A; Holst, John M; Hou, Peter C; et al. (The New England journal of medicine, 2018)
Differentiating acute bacterial infection from other causes of lower respiratory tract illness is challenging. In this trial, procalcitonin was investigated as a point-of-care test to aid in determining whether antibiotics were needed in the treatment of these illnesses.